Modernità ‘primitivista’: dopo gli indiani, i neri. - Pesavento, Sandra Jatahy (Confluenze. Rivista di Studi Iberoamericani, 2009)
The concept of primitive, besides that one of identity that cross it, is a social construction, a collective representation founded in a relationship between a “we” and a “others”. It’s not possible to contend that a people is primitive in his own nature, because this concept is built with images and discourses, narratives, that put in contrast the world of those ones that analyze and those ones that are analyzed. In this way, the paper presents the discussion – in the process of construction of a Brazilian national identity, between the Nineteenth and Twentieth centuries – concerning the sign of the primitive that brand the Indians and Black people presence in this formative path of “Brazilianity”. Beginning with a negative perception about the difference, in the Nineteenth Century thought, its comes – in the Twenties – to a positive understanding about the Brazilian cultural diversity, in the modernism ideas and in the Gilberto Freyre’s analysis. The Freyre sociological approach allow us to think about the frontiers present in a world without frontiers and show us that the boundaries – as imaginaries constructions of the society – are part of the social imaginary. I concetti di primitivo, così come quello di identità che lo attraversa, sono costruzioni sociali, rappresentazioni collettive fondate su un rapporto fra un “noi” e un “altri”. Non si può affermare che un popolo è primitivo nella sua natura, perché questo concetto è forgiato a partire da immagini e discorsi, narrative, che contrappongono il mondo di chi analizza e di chi è analizzato. In questo senso, il saggio si propone di discutere – nel processo di costruzione dell’identità nazionale brasiliana, fra l’Ottocento e il Novecento – il segno del primitivo che stigmatizza la presenza degli indios e dei neri in questo percorso formativo della “brasilianità”. Partendo da una percezione negativa della differenza, nel pensiero del secolo XIX, si approda – dagli anni ‘20 – ad una lettura positiva della diversità culturale del Brasile, sia nel modernismo che nell’analisi di Gilberto Freyre. Lo sguardo sociologico di Freyre, ci permette di pensare alle frontiere presenti in un mondo senza frontiere e ci fa capire che i confini – in quanto costruzione anche immaginarie della società – fanno parte dell’immaginario sociale.